Quantum Cryptography: Principle and Applications - Kumari, Sumit; Kumar, Anil (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Quantum cryptography is groundbreaking way to make communication super secure using science of quantum mechanics. Solving hard math problems to keep thing safe, quantum cryptography uses the laws of nature making it much harder for anyone, even powerful quantum computer to break. BB84 and E91 are Special recipes help set up secure communication using quantum mechanics. Quantum cryptography examines real -world implementations, current challenges and potential future directions including post-quantum cryptography and quantum networks. Quantum cryptography could redefine cybersecurity by combining cutting-edge science with innovative technology to protect sensitive information.